1995
DOI: 10.1136/gut.36.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine phenotyping of cytochrome P4501A2, N-acetyltransferase, and xanthine oxidase in patients with familial adenomatous polyposis.

Abstract: Patients with familial adenomatous polyposis (FAP) and age and sex matched controls were tested for cytochrome P4501A2 (CYP1A2), N-acetyltransferase, and xanthine oxidase activities using caffeine urinary metabolites as a discriminator. FAP patients showed significant underactivity of N-acetyltransferase (which inactivates some carcinogens) and significant overactivity of CYP1A2 (which activates some carcinogens). Xanthine oxidase activity, which can generate free radicals and cause cellular damage, was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Other conditions in which XOR activity and COX-2 have been tentatively linked include patients with familial adenomatous polyposis. Polypoid lesions in this disease have been demonstrated to have elevations in XO activity 25 as well as COX-2. 26 Indeed, the COX-2 inhibitor Celecoxib has been approved for treatment of these individuals as a therapy for polyp regression.…”
Section: Discussionmentioning
confidence: 93%
“…Other conditions in which XOR activity and COX-2 have been tentatively linked include patients with familial adenomatous polyposis. Polypoid lesions in this disease have been demonstrated to have elevations in XO activity 25 as well as COX-2. 26 Indeed, the COX-2 inhibitor Celecoxib has been approved for treatment of these individuals as a therapy for polyp regression.…”
Section: Discussionmentioning
confidence: 93%
“…[9] in colorectal cancer patients, as well as those from Spigelman et al. [28] in familial adenomatous polyposis (FAP) patients. In both studies, patients had higher CYP1A2 activity using caffeine as a probe than controls, although the difference was only slight in the investigation by Lang et al.…”
Section: Discussionmentioning
confidence: 99%
“…24 iNOS catalyzes the conversin of L-arginine to L-citrulline and the liberation of diffusion highly reactive nitric oxide species, an array of unstable chemical forms reminiscent of ROS and characteristic of an oxido-reductive imbalance. 25 (v) In familial adenomatous polyposis (FAP) patients, an increase in the free radical generating enzyme xanthine oxidase 26 and a decrease in antioxidant capacity was found. 27 Moreover, Bras et al 28 reported that prooxidant status (lipid peroxidation) is statistically increased was higher and antioxidant status (ascorbate and catalase activities ) was reduced.…”
Section: Discussionmentioning
confidence: 99%